Kecemburuan sosial remaja dalam film yowis ben berdasarkan perspektif sosiologi georg simmel - dewi, devira kumala (Maliki Interdisciplinary Journal, 2025)
Social jealousy is a complex phenomenon that frequently arises among adolescents, particularly in the context of economic disparity and social pressure. The film Yowis Ben by Bayu Skak and Fajar Nugros presents a narrative that illustrates the social conflicts experienced by the main character, Bayu, in his journey to become a musician. This article aims to analyze the forms of social jealousy in the film Yowis Ben using Georg Simmel’s theory of social interaction. This study employs a descriptive qualitative approach, utilizing content and narrative analysis techniques on film scenes and dialogues. The findings reveal that social jealousy emerges due to economic inequality but also fosters solidarity and collective spirit among teenagers. This study concludes that social conflict, rather than being purely destructive, serves as a mechanism of social integration, as theorized by Simmel.